2014
DOI: 10.1007/s00396-014-3404-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between helical aggregates and polymorphs in a 12-hydroxystearic acid gel: their thermal stability and formation kinetics

Abstract: Structures of 12-hydroxystearic acid (12-HSA)/ phenyl methyl silicone gel and the gelation process were investigated by means of synchrotron small-angle X-ray scattering (SAXS), wide-angle X-ray scattering (WAXS), and polarized optical microscopy (POM). Spherulite structures were formed at low temperatures, while helical aggregates without branching were observed at high temperatures. The morphological transformation from spherulites into helical aggregates occurred during a heating process but not vice versa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Recently it has been reported that different polymorphs were formed for 12-HSA gels in different solvents [13]. More recently, we reported that different polymorphs appeared at different temperatures [14], for example, three (001) peaks ( 1,(001) , 2,(001) , and 3,(001) ) corresponding to long spacings of 46.5, 42.4, and 39.7Å, respectively, were observed for 12-HSA gels in phenylmethyl silicone and for a neat HSA prepared by a temperaturejump into different temperatures, and each crystal form was termed form I, form II, and form III [14]. Contrary to it, a different behavior was observed for 12-HSA gel in a different solvent; for example, our small-angle neutron scattering (SANS) and synchrotron SAXS studies revealed that the selfassembled structure of 12-HSA in toluene was not affected by concentrations of the gelator and temperatures, [15][16][17].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Recently it has been reported that different polymorphs were formed for 12-HSA gels in different solvents [13]. More recently, we reported that different polymorphs appeared at different temperatures [14], for example, three (001) peaks ( 1,(001) , 2,(001) , and 3,(001) ) corresponding to long spacings of 46.5, 42.4, and 39.7Å, respectively, were observed for 12-HSA gels in phenylmethyl silicone and for a neat HSA prepared by a temperaturejump into different temperatures, and each crystal form was termed form I, form II, and form III [14]. Contrary to it, a different behavior was observed for 12-HSA gel in a different solvent; for example, our small-angle neutron scattering (SANS) and synchrotron SAXS studies revealed that the selfassembled structure of 12-HSA in toluene was not affected by concentrations of the gelator and temperatures, [15][16][17].…”
Section: Introductionmentioning
confidence: 74%
“…This result suggests that form II or form III was transformed into form I during the aging period. Thus, it has been shown that form I is most stable at RT for the ionogel, which is the same as a result of 12-HSA/phenylmethyl silicone gel [14]. However, the rate of the transformation from form II into form I for the ionogel was faster than that of 12-HSA/phenylmethyl silicone gel.…”
Section: Stability Of Crystal Forms In Gelsmentioning
confidence: 89%
See 2 more Smart Citations
“…The morphology of the gelator fibres can be influenced by the solvent. 12‐HSA can exist as different polymorphs which is also known to affect the morphology of the fibres ,…”
Section: Resultsmentioning
confidence: 99%